Politeianieuws : maandelijks tijdschrift voor de Staats- en Sociale Wetenschappen. (Gent : Politeia.)
Fonds Suzan Daniel (FSD)
Periodiciteit : ?
Redactie : Gezusters Lovelingstraat 24, 9000 Gent
Nederlands
Periodiek